Determination of Service Centre in Parakan Urban Area of Temanggung Regency - Yesiana, Reny; Astuti, Khristiana Dwi; Imawati, Dessy; Nurpratama, Dhafa Yoga; Puspita, Delia (Universitas Islam Sultan Agung Semarang, 2024)
The determination of an areas interrelated services is found in urban areas. The spatial structure that will encourage sustainable development in the region is a dynamic process of space utilization change. Parakan District is a sub-district in Temanggung Regency that has been designated as the Parakan Urban Area, to optimize its urban development by determining the determination of service centers. Data methods in the study used primary and secondary data, namely facilities, road infrastructure, trade and services and buildings. The analysis method used to determine the density hierarchy is through kernel density. The final results of the research are density scoring and weighted overlay to determine the service center of the Parakan Urban Area which consists of two villages and eleven villages. The determination of service centers in the Parakan Urban Area is divided into three hierarchies, including city/urban service centers, sub-city/urban service centers and sub-district/village neighborhood centers by considering the existing and estimated development of the area